Evaluation of Relative Isotopic Abundance Measurements in a Quadrupole Time-of-Flight Mass Spectrometer for Elemental Composition Determination of Natural Products in Traditional Chinese Medicine. Issue 2 (April 2013) - Wu, Zhi-Jun; Huo, Jia-Li; Chen, Jian-Zhong; Li, Na; Fang, Dong-Mei; Chen, Xiao-Zhen; Zhang, Guo-Lin; Wang, Jian-Hua; Xu, Xiao-Ying
The relative isotopic abundance (RIA) measurement errors of a quadrupole time-of-flight (Q-ToF) instrument incorporating analog-to-digital converter detectors were systemically evaluated by stochastically collecting about 200 data in positive ion mass spectrometry (MS) mode. Errors varied with peak intensities at definite spectral acquisition rates but were very close, even if peak intensities changed sharply at different spectral acquisition rates with the same concentration. Intensity thresholds were systematically defined at 1 Hz of spectral acquisition rates. RIA measurement errors were also evaluated using peak area. It seemed that peak area was better adapted for the high-intensity ions while peak intensity was suited for very low-intensity ions. Several known compounds were selected for RIA measurements for product ions in tandem mass spectropmetry (MS/MS) mode. An extract of a representative traditional Chinese medicinal, Paederia scandens was analyzed with high-performance liquid chromatography-electrospray ionization-QToF-MS/MS. The unique elemental compositions of some compounds could not be identified even with exact masses and MS/MS spectra of measured and reference compounds. RIA errors, especially of (M + 2)M −1, provided vital information for determining the elemental composition.